Необходимые условия оптимальности второго порядка в задачах оптимального управления, описываемых системой интегродифференциальных уравнений типа Вольтерра - Мансимов, К.Б.; Марданов, М.Дж. (Проблемы управления и информатики, 2013)
Розглянуто задачу оптимального керування, описану системою інтегродиференціальних рівнянь типу Вольтерра. Вважаючи область керування відкритою, виведено необхідну умову оптимальності у формі рівняння Ейлера. При дослідженні другої варіації критерію якості встановлено різні необхідні умови оптимальності другого порядку, виражені параметрами поставленої задачі. Вивчено випадок виродження аналога умови Лежандра–Клебша. Доведено багатоточкові необхідні умови оптимальності особливих в класичному сенсі керувань. An optimal control problem described by a system of Volterra type integro-differential equations is considered. Under the assumption of openness of the controlled domain, the necessary optimality condition is derived in the form of Euler’s equation. Further, by investigating the second variation of the performance criterion, different necessary optimality conditions of second order expressed by the parameter of the stated problem are established. In particular, the case of degeneration of the analog of Legandre–Klebsh condition is studied. Numerous necessary optimality conditions of singular in the classic sense controls are proved.